Resistance of pea varieties to aschochyta blight in varying environmental сonditions - T. P. Gradoboeva (Аграрная наука Евро-Северо-Востока, 2017)
Results of estimation of resistance level and adaptive potential of pea varieties against aschochyta blight in infectious background under varying weather conditions for 2013-2016 (HTC from 0.70 up to 1.61). Two hundred and eighty two varieties of pea of domestic and foreign breeding were analysed. During investigation period 11.8% of varieties had resistance to black-spot aschochytosis estimated by beans, and 5.0% - to light-spot one. Resistance of beans and high resistance of seeds to light-spot aschochytosis (Е-182, Д-23417, and Е-3767) and dark-spot aschochytosis (Verkholuzskaya, Е-413, Е-3588, Е-3923, and Е-3598) was revealed. This trait was more stable in varieties Stabil (V = 14.9%), Е-3923 (V = 25.1%), D-23417 (V = 44.1%), and Е-3767 (V = 45.1%). These varieties may be used in breeding as sources of resistance to disease. Most part of varieties selected by resistance to aschochytosis belongs to intensive type varieties (bi>1). Varieties Ryabchik, Е-246, Valleg Fanndation, and D-23417 weakly react to change of environmental factors (bi